A radicalidade do Art. 769 da CLT como salvaguarda da Justiça do Trabalho = The radicality of the Article 769 from CLT (Consolidated Labor Laws) as safeguard of the Labor Couurts - Souto Maior, Jorge Luiz (2016)
Disponível também na Revista Síntese: Trabalhista e Previdenciária, São Paulo, v. 27, n. 317, p. 33-47, nov. 2015.